MOF‐Enabled Ion‐Regulating Gel Electrolyte for Long‐Cycling Lithium Metal Batteries Under High Voltage. Issue 9 (15th December 2021) - Fu, Xuewei; Hurlock, Matthew J.; Ding, Chenfeng; Li, Xiaoyu; Zhang, Qiang; Zhong, Wei‐Hong
Abstract: High‐voltage lithium metal batteries (LMBs) are a promising high‐energy‐density energy storage system. However, their practical implementations are impeded by short lifespan due to uncontrolled lithium dendrite growth, narrow electrochemical stability window, and safety concerns of liquid electrolytes. Here, a porous composite aerogel is reported as the gel electrolyte (GE) matrix, made of metal–organic framework (MOF)@bacterial cellulose (BC), to enable long‐life LMBs under high voltage. The effectiveness of suppressing dendrite growth is achieved by regulating ion deposition and facilitating ion conduction. Specifically, two hierarchical mesoporous Zr‐based MOFs with different organic linkers, that is, UiO‐66 and NH2 ‐UiO‐66, are embedded into BC aerogel skeletons. The results indicate that NH2 ‐UiO‐66 with anionphilic linkers is more effective in increasing the Li + transference number; the intermolecular interactions between BC and NH2 ‐UiO‐66 markedly increase the electrochemical stability. The resulting GE shows high ionic conductivity (≈1 mS cm −1 ), high Li + transference number (0.82), wide electrochemical stability window (4.9 V), and excellent thermal stability. Incorporating this GE in a symmetrical Li cell successfully prolongs the cycle life to 1200 h. Paired with the Ni‐rich LiNiCoAlO2 (Ni: Co: Al = 8.15:1.5:0.35, NCA) cathode, the NH2 ‐UiO‐66@BC GE significantly improves the capacity, rate performance, and cycle stability, manifesting its feasibility to operate under high voltage. Abstract : A MOF@bacterial cellulose gel electrolyte to stabilize lithium metal batteries under high voltage is developed. The composite gel electrolyte is fabricated by embedding anionphilic, mesoporous NH2 ‐UiO‐66 into 3D bacterial cellulose aerogel, enabling to regulate uniform ion deposition to fundamentally prevent the formation of lithium dendrites. The gel electrolyte remarkably improves the electrochemical performance of symmetric lithium cells and high‐voltage cathodes.